ØªÙ†Ù…ÙŠØ© Ø§Ù„ÙˆØ§Ø³Ø·Ø© Ø§Ù„ØªÙØ§Ø¹Ù„ÙŠØ© Ø¨Ø¹Ø±Ø¶ ØªÙ‚Ø¯ÙŠÙ…ÙŠ Ø¹Ù„Ù‰ Ù…ÙˆØ§Ø¯ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Suaidi Suaidi (Lughatu Ad-dhat, 2020)
The research used is Research and Development. Where this method is used to produce certain products and test the effectiveness of these products. This research instrument test uses the validity and reliability test. The results of the validity test of 15 test items, there are 12 valid items and 3 invalid and reliable items with a reliability coefficient of 0.820. Furthermore, the data were tested with the "t" test with paired samples - T test to find out the pre-test and post-test significance and to find out the effect or influence of interactive powerpoint media on Arabic. The calculation results show that the significance is 0,000 <0.05, then H0 is rejected and Ha is accepted. So it can be concluded that there is an average difference between pre-test learning outcomes and post-test, which means there is an influence of the use of interactive powerpoint media on Arabic subjects in class XI MA NW korleko in the academic year 2019/2020.Powerpoint